Development and Characterization of Polystyrene Eco-composites Reinforced with Australian Royal Palm (Archontophoenix alexandrae) Stem Fibers - Mariana Oliveira Grossi; Débora Fernandes Silvério; Raiane Ribeiro Machado Gomes; Rodrigo Lassarote Lavall; Cláudio Mudado Silva; Stéphani Caroline de Lana Arêdes; Marcelo Moreira da Costa; Cassiano Rodrigues de Oliveira (Floresta e Ambiente, 2024)
Abstract Given escalating environmental concerns and stricter regulations, there’s a pressing need for sustainable materials. Eco-composites, which blend natural fibers with polymer matrices for reinforcement, are gaining traction. This study stands out by employing Australian royal palm stem fibers within a polystyrene matrix for eco-composites. The research involved assessing thermal stability, quantifying lignin/carbohydrate content, and measuring moisture levels. Scanning electron microscopy was utilized to examine fiber structure. Results from evaluations of thermal and mechanical properties underscore the high-performance reinforcement potential of Australian royal palm fibers, suggesting their suitability for various eco-composite applications. Beyond meeting the demand for sustainable materials, this project introduces an innovative use of these fibers, broadening their potential applications and advocating for greener, socially responsible industry practices.